Pengembangan Video Powtoon Berbasis Saintifik untuk Siswa Kelas V SD Muhammadiyah 8 Surabaya - Deni Adi Putra (Universitas Kanjuruhan Malang, 2021)
This study aims to produce valid, practical, and effective scientific-based powtoon videos. The development model used in this study is a 4-D model. The results of media validation by material experts are 88%, media experts are 93% with the